Factors influencing on the living standard of the cultivators: a study with reference to katsilaimadu grama niladhari division of mullaitheevu district - Mayusa, S.; Vijayakumar, S. (Proceedings of 9th International Symposium, 2019)
This study is based on the factors influencing on the living standard of cultivators of Katsilaimadu Gradma Niladhari Division of Mullaitheevu District. The aim of this study is to identify the determinants mostly influencing on the living standard of the cultivators. To carry out this study, the qualitative and the quantitative approaches are used. The primary and the secondary data are used in this study. The primary data are collected by using questionnaires. A number of 77 agrarian families are selected as sampling under proportionate method. The structured questionnaires are administrated among the sample size to collect the data. By analyzing the collected data, the conclusions are drawn. The secondary data are collected from the reports of the respective departments in study area. It is found from the analysis that income affects the living standard of cultivators. The estimated value of R2 is equal to 0.668. Accordingly, the independent variables such as Savings, the amount of loan, the income from the production of paddy cultivation, the income from the assets, the income from abroad, and other income influence by 67% (0.668) on the living standard of the cultivators. Other factors not included in the independent variables influences by 33% on the living standard of the cultivators. 1% of the increase in the income generated from the production of paddy cultivation increases the living standard of the cultivators by 63.2%. 1% of the increase in the income generated from the other employment excluding the income from the production of paddy cultivation leads to increase the living standard of the cultivators by 37.5%. At the same time, one percent of the increase in the amount of loan decreases the living standard of the cultivators 0.158 units and P- values of other variables such as savings, the income from assets, and the income from abroad are estimated at 0.354, 0.8980, and 0.670 respectively. As these values are higher than 5% of confidence interval, it is concluded that these factors don’t effect on the living standard of the cultivators.
Keywords: Living standard; Production of paddy cultivation; Cultivators; Economy